Þorramatur - Gísladóttir, Hallgerður (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2000)
Þorramatur is a name that has been given to the kinds of traditional Icelandic food that is served in the midwinterfeasts called Þorrablót (during the old month Þorri) in Iceland. In the fifties, there was an upswing in these feasts and then restaurateurs began using the name Þorramatur when advertising these dishes. Since then, many of the food stuffs that Þorramatur consists of are almost only seen in the supermarket at Þorri month and those who are most rare in other seasons tend to be "more" Þorramatur than the others. This applies to the dishes that are soured in whey, which are getting rare now, especially in towns. But when the denomination Þorramatur was invented, it was rather rare to see these dishes in Þorrablót because at that time they were everyday food in most places. In the last years some new dishes have been added to Þorrablót mostly to satisfy young people that go to Þorrablót but do not like the traditional food.